2019
DOI: 10.1161/strokeaha.119.025520
|View full text |Cite
|
Sign up to set email alerts
|

Misdiagnosis Worsens Prognosis in Subarachnoid Hemorrhage With Good Hunt and Hess Score

Abstract: Background and Purpose— Our aim was to describe variables associated with initial misdiagnosis of subarachnoid hemorrhage (SAH). We also analyzed the relationship of misdiagnosis with poor outcome and complications in good Hunt and Hess (HH) cases. Methods— In a prospective cohort of 401 patients with SAH, misdiagnosis was defined as failure to correctly identify, at first physician contact, a subsequently documented SAH; this meant no urgent radiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 14 publications
0
22
1
Order By: Relevance
“…For endovascular therapy, a grading system named Changhai score worked well on the aSAH clinical outcome prediction (21), of which the 4 pronounced risk factors including age, HH grade, mFS, and aneurysm location were identical to these findings. Although the HH grade and mFS have been widely used to evaluate the severity and outcome of aSAH in clinical practice, these evaluation scales have many limitations which could lead to the initial misdiagnosis due to the subjectivity of the neuro interventionalists or the adjudicated information (27,28). Hence, it may be useful to take other preoperative factors into account for better predictions.…”
Section: Discussionmentioning
confidence: 99%
“…For endovascular therapy, a grading system named Changhai score worked well on the aSAH clinical outcome prediction (21), of which the 4 pronounced risk factors including age, HH grade, mFS, and aneurysm location were identical to these findings. Although the HH grade and mFS have been widely used to evaluate the severity and outcome of aSAH in clinical practice, these evaluation scales have many limitations which could lead to the initial misdiagnosis due to the subjectivity of the neuro interventionalists or the adjudicated information (27,28). Hence, it may be useful to take other preoperative factors into account for better predictions.…”
Section: Discussionmentioning
confidence: 99%
“…More than 30% of survivors may develop severe disability and delayed neurological dysfunction due to complications such as delayed cerebral ischemia (DCI) and rebleeding ( 3 ). The progression of aSAH is individualized and rapid, so accurate risk stratification and prognosis prediction is challenging ( 4 ). A growing body of research has found that neuroinflammation and immune disorders after aSAH may play an important role in both early brain injury (EBI) and delayed neurological injury ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although aneurysmal SAH accounts for 5-10% of all strokes in the United States 3 , it may cause significantly high mortality 4 , and the survivors may suffer from long-term neuropsychological effects and decreased quality of life 5 . Early diagnosis of underlying IAs can both influence clinical management and guide prognosis in intracerebral hemorrhage patients 6,7 . For patients with spontaneous SAH, timely and accurate identification of IAs is critical for immediate intervention or surgical management, whereas for patients without IAs, reliable exclusion of IAs is also important for specialized management 8 .…”
mentioning
confidence: 99%